PENERAPAN MODEL DISCOVERY LEARNING DALAM PEMBELAJARAN IPA TEMATIK DI SEKOLAH DASAR - Nelvianti Nelvianti; Widya Indra; Rauladety Anas; Yanti Fitria; Desyandri Desyandri (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2020)
This study aims to provide an overview of the application of discovery learning models in thematic science learning in State Elementary School 01 Pakan Rabaa, Solok Selatan Regency. The background of this research is the importance of teachers knowing the steps in applying discovery learning models in thematic science learning in order to create science learning that is not only oriented towards results or products but also processes. This research uses a qualitative approach with descriptive methods. Data on teacher opinions were collected through interviews. Data in the form of interviews, observations and documentation were analyzed descriptively. Data analysis is performed through data collection, reduction, presentation and conclusion drawing. The subjects of this study were the teachers of State Elementary School 01 Pakan Rabaa, Solok Selatan Regency. Based on the results of data analysis, it was found that thematic science learning with discovery learning models can involve students to develop knowledge and skills in solving problems, so that by applying discovery learning models can make students who are initially passive become more active and creative.Keywords: Discovery learning model, thematic science, elementary school